Arguments Against Marriage Equality: Commemorating & Reconstructing Loving v. Virginia - Tucker Culbertson (Washington University Law Review, 2007)
The year 2007 marked the fortieth anniversary of Loving v. Virginia, in which the Supreme Court denounced antimiscegenation law and policy. I argue here that Loving was wrongly decided. I argue against the fundamental right to marriage declared in Loving, and offer alternative interpretations of the harms and rights at issue in the case.
Keywords: Discrimination; Critical legal studies; Human rights; Marriage; Loving v. Virginia; 87 S. Ct. 1817 (1967)